Effect of Free Nutritious Meals on Qur’an Hadith Learning Interest via Motivation - Rendy S. Sambara; Najamuddin Petta Solong; Mardeli Mardeli; Apriliyanus Rakhmadi Pratama; Zohra Yasin; Gesika Avelina; Ahmad Fakhrurrazi bin Mohammed Zabidi (ZAD Al-Mufassirin, 2026)
At MA Al-Falah, Gorontalo, students’ interest in Qur’an-Hadith learning remains low despite the implementation of the Free Nutritious Meal Program, which provides daily healthy meals to support students’ physical readiness. This study examined the effect of this program on students’ learning interest, with learning motivation as a mediating variable, grounded in Maslow’s hierarchy of needs and Self-Determination Theory (SDT). Conducted with a total sample of 104 students, , data were collected via a four-point Likert-scale questionnaire and analyzed using path analysis. Results revealed that the program did not significantly influence learning motivation (β = 0.116, p = 0.243) or learning interest (β = 0.113, p = 0.119), whereas learning motivation significantly affected learning interest (β = 0.673, p < 0.001). Mediation analysis indicated that learning motivation did not mediate the program’s effect. These findings highlight that intrinsic motivation is the dominant factor in fostering students’ interest in Qur’an-Hadith learning. While nutritional programs support students’ physical readiness, enhancing learning interest requires pedagogical strategies that foster intrinsic motivation, experiential engagement, and spiritual-emotional involvement.